Maintenance and recall of memory T cell populations against tuberculosis: Implications for vaccine design - Liu, Xin; Li, Haoran; Li, Shanshan; Yuan, Jinfeng; Pang, Yu (Frontiers in Immunology, 2023)
Despite the widespread use of standardised drug regimens, advanced diagnostics, and Mycobacterium bovis Bacille-Calmette-Guérin (BCG) vaccines, the global tuberculosis (TB) epidemic remains controllable. To address this challenge, improved vaccines are urgently required that can elicit persistent immunologic memory, the hallmark of successful vaccines. Nonetheless, the processes underlying the induction and maintenance of immunologic memory are not entirely understood. Clarifying how memory T cells (Tm cells) are created and survive long term may be a crucial step towards the development of effective T cell–targeted vaccines. Here, we review research findings on the memory T cell response, which involves mobilisation of several distinct Tm cell subsets that are required for efficient host suppression of M. tuberculosis (Mtb) activity. We also summarise current knowledge related to the T cell response-based host barrier against Mtb infection and discuss advantages and disadvantages of novel TB vaccine candidates.